Muscarinic M2 receptors directly activate Gq/11 and Gs G-proteins - Michal, P; El-Fakahany, E E; Dolezal, V (The Journal of pharmacology and experimental therapeutics, 2007)
Muscarinic M(2) receptors preferentially couple with the G(i/o) class of G-proteins to inhibit cAMP synthesis. However, they can also stimulate net synthesis of cAMP and inositol phosphate (IP) accumulation. We investigated in intact Chinese hamster ovary (CHO) cells expressing human M(2) receptors (CHO-M(2) cells) whether direct interaction of M(2) receptors with G(s) and G(q/11) G-proteins is responsible for the latter effects. Suppression of the G(s)alpha subunit using RNA interference abolished stimulation of cAMP synthesis induced by 1 mM carbachol in both control and pertussis toxin-treated CHO-M(2) cells but had no effect on the inhibition of forskolin-stimulated cAMP synthesis. Carbachol stimulated accumulation of IP with an EC(50) of 79 microM. Removal of the G(q),G(11), or both alpha subunits reduced this response by 78, 54, and 92%, respectively, whereas suppression of the G(s)alpha subunit had no effect. Similar results obtained in CHO cells expressing M(1) receptors that preferentially couple with G(s) and G(q/11) G-proteins confirmed the efficiency of siRNA treatments. Stimulation of M(2) receptors in control and pertussis toxin-treated cells by a series of full agonists with respect to inhibition of adenylyl cyclase displayed different efficacies in stimulating IP accumulation. Carbachol, acetylcholine, and oxotremorine-M [N,N,N-trimethyl-4-(2-oxo-1-pyrolidinyl)-2-butyn-1-ammonium] behaved as full agonists, furmethide (N,N,N-trimethyl-2-furanmethammonium) and methylfurmethide [(5-methyl-2-furyl)methyltrimethylammonium] were partial agonists, and oxotremorine (1-[4-(1-pyrrolidinyl)-2-butynyl]-2-pyrrolidinone) had no effect. Our results provide direct evidence of M(2) receptor coupling with the alpha subunits of G(s) and G(q/11) G-proteins and demonstrate induction of multiple receptor conformational states dependent on both the concentration and the nature of the agonist used.
Keywords: receptor muskarinový M2; Cyclic AMP; Inositol Phosphates; CHO buňky; proteiny vázající GTP - alfa-podjednotky Gq-G11; inositolfosfáty; Animals; RNA, Small Interfering; GTP-Binding Protein alpha Subunits, Gq-G11; Receptor, Muscarinic M2; AMP cyklický; Cricetulus; křečci praví; malá interferující RNA; GTP-Binding Protein alpha Subunits, Gs; Cricetinae; CHO Cells; zvířata; proteiny vázající GTP - alfa-podjednotky Gs